Ultrasound guided diagnosis of anoestrus and its treatment in postpartum crossbred Holstein-Friesian cows (Bangladesh Veterinarian, 2019)
This study was undertaken to determine the feasibility of using ultrasonography for diagnosis of postpartum anoestrus followed by its effective management and treatment in crossbred (Holstein-Friesian X zebu) cows. A total of 57 crossbred lactating cows with unobserved oestrus for ≥60 days postpartum was examined by ultrasonography at Central Cattle Breeding and Dairy Farm (CCBDF), Savar, Dhaka. Cows were divided into silent oestrus and true anoestrus groups by ultrasonography. The pregnancy was diagnosed transrectally using ultrasonography 28 - 35 days after AI. Cows with silent oestrus were treated with Cloprostenol (500 μg) followed by AI or with 2 doses of Cloprostenol 10 days apart followed by AI at observed oestrus. The true anoestrus cows were supplied with anthelmintic and vitamin ADE injection with balanced nutrition, treated with Gonadorelin (500 μg) followed by AI or with Gonadorelin followed by injecting Cloprostenol at 7 days interval and AI at observed oestrus. All cows with silent oestrus and true anoestrus were divided into different body condition score (BCS), milk yield, age and parity groups to determine their influence on outcome of treatment. Out of 57 anoestrus cows examined, 56% were confirmed as silent oestrus and 44% were confirmed as true anoestrus. In silent oestrus, 71% cows showed cyclicity and 43% became pregnant after treatment with Cloprostenol and 78% cows showed cyclicity and 50% became pregnant after treatment with 2 doses of Cloprostenol 10 days interval (P>0.05). In true anoestrus group, 60% cows showed cyclicity and 40% became pregnant when balanced diet was supplemented. Around 78% cows showed cyclicity and 44% became pregnant after treatment with Gonadorelin and 91% cows showed cyclicity and 55% became pregnant when Gonadorelin was followed by Cloprostenol at 7 days interval (P>0.05). Significant (P